Complexation of pectins varying in overall charge with lysozyme in aqueous buffered solutions. (September 2019) - Antonov, Yurij A.; Celus, Miete; Kyomugasho, Clare; Hendrickx, Marc; Moldenaers, Paula; Cardinaels, Ruth
Abstract: We examined how a particular structural characteristic of pectin, namely its degree of methoxylation (DM), affects its complexation with lysozyme (lys), whereby the phase behavior of the complex system as a whole as well as the aggregation state of the complex phase are considered. Low and medium methoxylated pectins bind lys at pH 5.1 and low ionic strength ( I  = 0.01) forming highly concentrated gel like complex particles, whereas highly methoxylated pectins undergo liquid/liquid phase separation with lys. "Mother" pectin with DM = 95.1% does not form complexes with lys. Highly charged pectins (low DM) already form complex particles at low pectin/lys weight ratios and have a high yield of the complex phase that consists of relatively large particles. The distribution of pectin within the complex particles has an irregular character for both pectin types. However, whereas for low DM pectin the complex composition reflects that of the mixture, the complex composition with high DM pectin is less sensitive to the mixture composition. Moreover, at low DM, the maximum complexation corresponds to charge neutralization whereas at high DM maximum complexation requires a larger than stoichiometric amount of lys. The minimal I and pH value at which complexation is completely suppressed, decreases with increasing DM of pectin, indicating the presence of electrostatic interactions in all systems. However, the differences in composition of the complexes and the protein/polysaccharide charge ratio at maximal complexation indicate that the exact binding mechanism depends on the pectin DM. Graphical abstract: Image 1 Highlights: Complexation of pectin with lys was observed only at DM less 95%. P66.5 and P77.7 formed liquid complex coacervates with lys. In the pH range from ∼5.2 to 6.2 complexation depended mainly on ID of pectins. Effect of I on complexation of highly charged pectin was not monotonic. Mechanism of binding was different for low and highly charged pectins.